Community, Ideology and Space: The Role of Local Governments in the Building of Community through Architecture in Çankaya and Keçiören - Demirel, Abdullah Eren (Ankara araştirmalari dergisi = Journal of Ankara studies, 2024)
The idea of community in sociospatial studies, which emerges from territorial explanations rooted in rural settlements, has become less well defined due to urbanization. In the complex structure of modern cities, while community can be generally considered in terms of the social networks of members, the territorial dimensions of living environments persist within the new generic city structure. This is because while the sense of community may be constructed socially through relations, the ideological territorial status remains instrumental, especially for local governments who define and control the physical boundaries of communities. This paper considers the tension between the ideological and social conceptions of community in an attempt to understand how the idea of community is spatially manifested by local governments. The paper also discusses how this manifestation leads to the instrumentalization of architecture by local governments in the construction of a particular sense of community and the enhancement of political influence. Accordingly, the spatial typologies for the construction of community proposed by the local governments of Çankaya and Keçiören – Çankaya Evi & Mahalle Konağı - are compared. In terms of socioeconomics and ideology, the two districts are historically two opposing poles in the capital of the Turkish Republic. This is clearly seen in the proposed symbolic, spatial, and programmatic community house typologies. The distinctive architectural symbols and namings by the two local governments of the community housing of both districts clearly exemplify the importance of the notion of community for local governments, as well as how the concept is utilized ideologically through spatial practices.